What we can learn about the behavior of firms from the average monthly frequency of price-changes: An application to the UK CPI data - Huw Dixon; Kun Tian (Cardiff University, Cardiff Business School, 2013)
The monthly frequency of price-changes is a prominent feature of many studies of the CPI micro-data. In this paper, we see how much this ties down the behavior of price-setters ("firms") in steady-state in terms of the average length of price-spells across firms. We are able to divide an upper and lower bound for the mean duration of price-spells averaged across firms. We use the UK CPI data at the aggregate and sectoral level and find that the actual mean is about twice the theoretical minimum consistent with the observed frequency. We estimate the distribution using the hazard function and find that although the estimated hazard differs significantly from the Calvo distribution, the means and medians are similar. However, despite the micro differences, we find that the artificial Calvo distributions generated using the sectoral frequencies result in very similar impulse responses to the estimated hazards when used in the Smets-Wouters (2003) model.
Keywords: E50; 330; price-spell; steady state; duration